An HSP90 cochaperone Ids2 maintains the stability of mitochondrial DNA and ATP synthase - Pei-Heng Jiang (BMC, 2021)
Abstract Background Proteostasis unbalance and mitochondrial dysfunction are two hallmarks of aging. While the chaperone folds and activates its clients, it is the cochaperone that determines the specificity of the clients. Ids2 is an HSP90’s cochaperone controlling mitochondrial functions, but no in vivo clients of Ids2 have been reported yet. Results We performed a screen of the databases of HSP90 physical interactors, mitochondrial components, and mutants with respiratory defect, and identified Atp3, a subunit of the complex V ATP synthase, as a client of Ids2. Deletion of IDS2 destabilizes Atp3, and an α-helix at the middle region of Ids2 recruits Atp3 to the folding system. Shortage of Ids2 or Atp3 leads to the loss of mitochondrial DNA. The intermembrane space protease Yme1 is critical to maintaining the Atp3 protein level. Moreover, Ids2 is highly induced when cells carry out oxidative respiration. Conclusions These findings discover a cochaperone essentially for maintaining the stability of mitochondrial DNA and the proteostasis of the electron transport chain—crosstalk between two hallmarks of aging.